TEACHING LEARNERS WITH READING DIFFICULTIES IN AN INCLUSIVE SETUP IN ZIMBABWE: CHALLENGES AND SOLUTIONS - CHIMHENGA, Dr. SYLOD (IJRDO- Journal of Educational Research, 2017)
The inclusion of all learners within the regular classroom has brought about a plethora ofchallenges for teachers. The purpose of this study was to explore the challenges faced bymainstream primary school teachers when teaching learners with reading difficulties in aninclusive education setup in Zimbabwe. The study used a combination of qualitative andquantitative methods of research. The study entailed a survey though questionnaires for thepurpose of gathering information on the challenges faced by mainstream primary schoolteachers when teaching learners with reading difficulties. The questionnaire was administeredon the teachers teaching dyslexic children in an inclusive set up. Fifty primary schoolteachers participated in the study. Participants were purposively selected from a group ofprimary school teachers teaching in inclusive set up who were willing to participate in thestudy. This study concluded that learners need to have their needs met concurrently with theirnon-dyslexic peers in an inclusive setting. The participants highlighted that parents did showan uncaring attitude like not helping learners with their homework or coming to the schoolsto inquire how best to help their dyslexic children. This study recommends there is need toprovide basic training of teachers on dyslexia to enable them to cope with differentiatededucation.